2018
DOI: 10.7189/jogh.08.020411
|View full text |Cite
|
Sign up to set email alerts
|

Medical research productivity in the Arab countries: 2007-2016 bibliometric analysis

Abstract: BackgroundThe aim of this study was to assess recent trends in medical research productivity in Arab countries.MethodsWe collected bibliometric data for the world countries, Arab countries, and Arab institutions for 2007-2016, using Essential Science Indicators, Journal Citation Reports, and Web of Science database. We collected the number of published papers overall and per year, citations per paper, and number of papers published in top quartile and top 10% journals. For the 10 most productive institutions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 21 publications
6
65
2
Order By: Relevance
“…Compared to overall medical research in the region, mental health research is lagging. While we found that mental health research increased from 0.7% of global output in 2009 to 1.2% in 2018, El Rassi et al (22) reported that overall medical research output in the same Arab region increased from 1.0% in 2007 to 2.1% of global output in 2016. Regional mental health research and overall medical research in general, however, share other characteristics: most of the research is published in low-impact local journals (ranging from 20 to 24% of total output) and about half of the studies are collaborative, most frequently with the same non-Arab countries (22).…”
Section: Key Trends In the Arab Regioncontrasting
confidence: 59%
“…Compared to overall medical research in the region, mental health research is lagging. While we found that mental health research increased from 0.7% of global output in 2009 to 1.2% in 2018, El Rassi et al (22) reported that overall medical research output in the same Arab region increased from 1.0% in 2007 to 2.1% of global output in 2016. Regional mental health research and overall medical research in general, however, share other characteristics: most of the research is published in low-impact local journals (ranging from 20 to 24% of total output) and about half of the studies are collaborative, most frequently with the same non-Arab countries (22).…”
Section: Key Trends In the Arab Regioncontrasting
confidence: 59%
“…20,21 In fact, El Rassi reported that the number of medical publications from the Arab region increased threefold between 2007 and 2016. 18 The increase in retractions in our study for the corresponding period was also nearly threefold, from 8 to 22: although we are comparing the numbers for medical publications to those for all publications, the proportion indicates that the Arab world contradicts the global trend of increasing number of retractions, described by Steen et al: 20 in other words, the increase in the number of retractions from the Arab region may reflect the overall increase in absolute terms but not in relative terms.…”
Section: Discussionmentioning
confidence: 99%
“…Aware that it has lagged behind, the Arab region is keen to step up its contributions to scientific literature and to bridge the regional and global gap. 18,19 Lest the pressure to publish should lead to misconduct and errors, eventually leading to retractions, it is important to highlight this threatwhich is why the present study sought to examine the current status of retractions from the Arab region.…”
Section: Introductionmentioning
confidence: 99%
“…Though the Middle East region has made signi cant advances in healthcare, the proportion of resources allocated to research and the research output is generally low in all elds, including critical care [1][2][3].…”
Section: Introductionmentioning
confidence: 99%